A coupled biomechanical-smoothed particle hydrodynamics model for predicting the loading on the body during elite platform diving - Harrison, S.; Cohen, R.; Cleary, P.; Barris, S.; Rose, G. (Applied Mathematical Modelling, 2016)
Large forces are imparted on the body during and after water entry when an athlete performs a platform dive. Injuries are common, especially in the arms, neck and back, and are thought to occur due to cumulative damage from many overload events as well singular cases of acute high loading events. Experimental measures of forces on the body are impractical and instead computational simulation is useful to estimate this loading. A coupled Biomechanical-Smoothed Particle Hydrodynamics (B-SPH) model for diver and water is developed and applied to a reverse pike dive performed by an elite athlete. The body surface is represented by a mesh that deforms in response to measured skeleton kinematics acquired from multi-camera video. Calculations of the fluid forces on the body and the transmission of torque through the upper body joints are made. The sensitivity of the results of the model to water entry pitch angle is explored. The simulation framework presented shows promise as a tool for coaches and sports scientists to evaluate the performance and safety of diving technique.